The Use of Code-Switching by The Speakers on Hima Lingua’s Webinar: Exploring Pedagogical and Affective Functions - Fradilla Sandi, Dita (Jurnal Sosial Teknologi, 2023)
Using more than one language in a sentence or discourse is called code-switching. Undeniably, it also occurs in the teaching and learning process in education. The latest era in education today is online learning, a system that can facilitate students learning more widely. Along with the growth of the online system, many kinds of platform offer learning tools, one of them is YouTube video-based platform. There are many educational-based videos on this platform. The researcher chose one of the video webinars uploaded by the student association channels. The purposes of this study were (1) To find out the types of code-switching in the webinar of Hima Lingua's YouTube video; (2) To explore the functions of code-switching in pedagogical and affective aspects in the webinar of Hima Lingua's YouTube video. The design of the study was content analysis. The research object was the video recording of the webinar uploaded to Hima Lingua's YouTube channel. In collecting the data, the author watched the video, transcribed it using Google docs, and then coded it using a software atlas—ti 9. The researcher used Ezzy's analysis model to analyze the data, which consists of transcription, condensation, identifying and grouping, and displaying the data. This study showed four types of code-switching, intra-sentential switching, inter-sentential switching, tag switching, and intra-word switching. Then, in pedagogical functions, the speaker mainly used code-switching for knowledge constructions. For affective functions, the speaker mostly used code-switching to maintain control. This study emphasizes the importance of using code language in the learning process as one of the ways to assist in more understanding, especially for classes that use two languages.